The moderate era in Indian politics Dadabhai Naoroji memorial prize fund lecture - Nanda, B. R. (Bal Ram), 1917-2010. (New Delhi ; Oxford : Oxford University Press, 1983)
The blurred and distorted image of the Moderate Era is partly due to the conscious superiority and almost contempt with which each generation tends to judge its predecessor. To understand the aims, methods, achievements, and limitations of the leaders of the Moderate Era in India, this lecture sets them in the changing political and social context of the times in which their lot was cast.
Description based on print version record.
Includes bibliographical references.
Keywords: India -- Politics and government -- 1765-1947.